Intranodal Angiomyomatous Hamartoma in a Cynomolgus Monkey. (February 2019) - Thirion-Delalande, Catherine; Gervais, Frédéric; Palate, Bernard; Forster, Roy; Schenka, André Almeida
We describe here an angiomyomatous hamartoma in the right axillary lymph node of a three-year-old male cynomolgus monkey ( Macaca fascicularis ), used as a control subject in a short-term toxicity study. This is a very rare lesion that has been reported almost exclusively in inguinal lymph nodes, and to date only in human beings. In the present case, light microscopy revealed partial replacement of the lymph node parenchyma by a disorganized, irregular vascular network, sparsely distributed smooth muscle cells, and a fibro-adipocytic stroma. This was considered to be fortuitous given the age of the animal, with no clinical or toxicological significance. To the best of our knowledge, this is the first report of an intranodal angiomyomatous hamartoma in a nonhuman animal species.